Generating Lexical Estimates in Academic Writing in English Using Technology: An Exploratory Study of Adult Indian Learners - Mukhopadhyay, Lina; Pillai, Sreelekshmi S. (Indian Journal of Educational Technology, 2024)
In this paper, we demonstrate how teachers can use a digital tool like Lexical Tutor to generate estimates or assessments of adult learners’ productive lexical knowledge in academic writing in English as a Second Language (ESL). The digital tool-generated lexical estimates are complemented by teacher feedback to illustrate the inductive method of language learning. In the first step, lexical estimates are created from a few samples of academic writing of adult ESL learners using Lexical Tutor. In the second step, it is employed to identify frequently used collocations in learners’ writing samples and then to create an illustrative bank of concordances based on available corpora. This sample of concordances can later be used to give feedback on usage rules of occurrences of lexical items within a variety of syntactic contexts. The feedback, it is hoped, would improve the content and coherence in academic writing by adding lexical richness and variety to the writing. Furthermore, the use of technology would help learners notice lexical features and improve the quality of writing in a self-regulated manner. This would also serve as an example of the inductive method of language learning.